2001
DOI: 10.1002/mus.1180
|View full text |Cite
|
Sign up to set email alerts
|

Severe autosomal recessive rippling muscle disease

Abstract: Rippling muscle disease (RMD) has previously been reported as a skeletal myopathy that was attributed to a defect in the sarcomere. Here we report a new form of RMD that is more severe, characterized by fatal arrhythmic cardiomyopathy and delayed bone age. Mortality has previously not been associated with RMD. With this report we hope to raise awareness that a subset of patients with this clinical entity are predisposed to severe cardiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 9 publications
0
12
1
Order By: Relevance
“…In one family with dominant RMD, the responsible gene was located on chromosome 1q41 [2]. RMD with autosomal recessive transmission associated with cardiac and bone involvement was recently described in two families from Oman [3]; rare sporadic forms of RMD associated with myasthenia gravis and thymoma presumably imply an autoimmune mechanism [4]. Betz et al [5] first demonstrated the association of autosomal dominant RMD with mutations in the caveolin-3 (Cav-3) gene; this molecular lesion is responsible for most cases of RMD.…”
Section: Introductionmentioning
confidence: 97%
“…In one family with dominant RMD, the responsible gene was located on chromosome 1q41 [2]. RMD with autosomal recessive transmission associated with cardiac and bone involvement was recently described in two families from Oman [3]; rare sporadic forms of RMD associated with myasthenia gravis and thymoma presumably imply an autoimmune mechanism [4]. Betz et al [5] first demonstrated the association of autosomal dominant RMD with mutations in the caveolin-3 (Cav-3) gene; this molecular lesion is responsible for most cases of RMD.…”
Section: Introductionmentioning
confidence: 97%
“…4,10 An autosomal-recessive form also exists. 5 Acquired RMD in association with myasthenia gravis (MG) was first reported in 1996, and this author is aware of seven patients reported to date. 3,7,14,15 Two of these patients were reported in a larger series of 77 patients with varied syndromes of neuromuscular hyperexcitability that included two previously reported patients.…”
mentioning
confidence: 94%
“…2,13 Severe forms of the disease, however, do exist. 5,6 The ripple propagates at approximately 0.6 m/s, which is 10 times slower than muscle fiber conduction velocities, and is typically electrically silent, suggesting the hypothesis that stretch of a muscle fiber results in the opening in neighboring fibers of sarcomeric mechanosensitive calcium channels, resulting in contraction of these fibers and repetition of the cycle. 8 Additional physical findings are myoedema, a localized mounding of muscle lasting for several seconds and induced by percussion, and "percussion-induced rapid contraction," a sign similar to percussion myotonia.…”
mentioning
confidence: 98%
“…Caveolin-3 gene mutations are also seen in patients with limb girdle muscular dystrophy 1C, distal myopathy and idiopathic hyperCKaemia. An autosomal recessive form also exists 3. Sporadic RMD is thought to be immune mediated 4 5 6.…”
mentioning
confidence: 99%